FREEZE-DRYING OF TEA LEAVES AT DIFFERENT PRESSURES: EFFECTS ON THE THIN-LAYER DRYING KINETICS, WATER ACTIVITY AND COLOR CHANGE - Muhammed Emin Topal; Birol SAHIN (Journal of Animal and Plant Sciences, 2025)
The primary purpose of this study is to freeze-drying (FD) of tea leaves (Camellia sinensis) and determine the drying kinetics using six different drying models. For this intent, a nonlinear regression analysis was conducted to evaluate four different criteria (R², r, χ², RMSE) and determine the best-fitting model for each pressure level based on the highest R² and r values and the lowest χ² and RMSE values. Fresh tea leaves farm in Rize, Türkiye were placed in a laboratory-scale freeze dryer and dried until the product reached equilibrium moisture. FD experiments were performed at three different cabin pressures (0.008, 0.010, and 0.012 mbar) to examine the effect of pressure variation on drying time and quality parameters. After analyzing the experimental results, it was determined that the Alibas model best describes the drying process of tea leaves at 0.008 mbar and 0.010 mbar pressure, while the Improved Midilli-Kucuk model is the most suitable at 0.012 mbar pressure. As a consequence of the FD process, it has been noted that the hue angle changed between 86.98-87.38 depending on cabin pressure, i.e. there was a transition in the color of tea leaves from green to red. The a* (Redness/Greenness) value changed from -6.2 in the fresh product to +1.3 in the final product. The highest drying rate of tea leaves occurred at the lowest cabin pressure. As a consequence of the FD experiment, the water activity of the tea leaves decreased (from 0.9800±0.0093 to 0.2901±0.0077) to a level where no microbial growth would occur.
Keywords: (Tea; Drying; Freeze-Drying; Drying kinetics)